2015
DOI: 10.1016/j.heares.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Canertinib induces ototoxicity in three preclinical models

Abstract: Neuregulin-1 (NRG1) ligand and its epidermal growth factor receptor (EGFR)/ERBB family regulate normal cellular proliferation and differentiation in many tissues including the cochlea. Aberrant NRG1 and ERBB signaling cause significant hearing impairment in mice. Dysregulation of the same signaling pathway in humans is involved in certain types of cancers such as breast cancer or non-small cell lung cancer (NSCLC). A new irreversible pan-ERBB inhibitor, canertinib, has been tested in clinical trials for the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Similarly, baseline synaptic firing of somatosensory neurons in EGF-like domain "knockout" mice is significantly above control levels. In contrast, these same Nrg1 models show deficits in evoked gamma oscillations induced by whisker stimulation (Barz et al 2014), auditory cues -albeit all Nrg1 mutant mice are known to have auditory abnormalities (Jin et al 2011;Kato et al 2015;Stankovic et al 2004;Tang et al 2015) -and the psychotomimetic, ketamine (Long et al 2015) whilst addition of Nrg1 in wild-type mice has been shown to enhance kainic-acid evoked gamma oscillations in prefrontal cortex (Hou et al 2014) and hippocampus (Fisahn et al 2009), the former in vivo and the latter in vitro. One study also suggests that excess Nrg1 may lead to similar impairments, as peak frequency, but not amplitude, of gamma oscillations were reduced in type I Nrg1 over-expressing mice (Deakin et al 2012), which also supports the inverted "U" model of Nrg1 function (Agarwal et al 2014;Law 2014;Talmage 2008).…”
Section: Nrg1 and Inhibitory Neurotransmissionmentioning
confidence: 99%
“…Similarly, baseline synaptic firing of somatosensory neurons in EGF-like domain "knockout" mice is significantly above control levels. In contrast, these same Nrg1 models show deficits in evoked gamma oscillations induced by whisker stimulation (Barz et al 2014), auditory cues -albeit all Nrg1 mutant mice are known to have auditory abnormalities (Jin et al 2011;Kato et al 2015;Stankovic et al 2004;Tang et al 2015) -and the psychotomimetic, ketamine (Long et al 2015) whilst addition of Nrg1 in wild-type mice has been shown to enhance kainic-acid evoked gamma oscillations in prefrontal cortex (Hou et al 2014) and hippocampus (Fisahn et al 2009), the former in vivo and the latter in vitro. One study also suggests that excess Nrg1 may lead to similar impairments, as peak frequency, but not amplitude, of gamma oscillations were reduced in type I Nrg1 over-expressing mice (Deakin et al 2012), which also supports the inverted "U" model of Nrg1 function (Agarwal et al 2014;Law 2014;Talmage 2008).…”
Section: Nrg1 and Inhibitory Neurotransmissionmentioning
confidence: 99%
“…To inhibit ErbB function following preganglionic surgery, mice were treated with canertinib [26] (LC Laboratories, #CI-1033) at 30 mg/kg body weight through daily intraperitoneal injections. Conversely, separate groups of mice were treated with different isoforms of NRG1 [27,28] at 0.12 mg/kg via daily subcutaneous injections to stimulate ErbB activity after postganglionic surgery.…”
Section: Pharmaceuticsmentioning
confidence: 99%
“…It also functions as a pan-ErbB receptor tyrosine kinase inhibitor, but does not inhibit v-Src. 25 27 …”
Section: Resultsmentioning
confidence: 99%